Project-based learning-STEAM model on students' critical thinking and scientific literacy: A bibliometric analysis - Iqbal Ainur Rizki; Woro Setyarsih; Nadi Suprapto (Jurnal Penelitian Ilmu Pendidikan, 2022)
This study analyses the application of the Project-Based Learning-STEAM (PjBL-STEAM) learning model to improve students' critical thinking skills and scientific literacy, especially in Indonesia, so the latest trends and research opportunities on these topics can be obtained. This study uses a quantitative bibliometric approach. The number of publications analyzed was 142 publication documents in 2015-2020, metadata was obtained from the Scopus database and analyzed using VOSviewer software. The results of metadata extraction show that there are 5 clusters with keywords that appear the most students, engineering education and STEM education. In addition, only 0.5% of authors have more than two publications, so further research from previous publications on this topic is still minimal. Based on the ranking results, the United States ranks 1st, Indonesia ranks 2nd, and Australia ranks 3rd. Indonesia is excellent in research development and collaboration on this topic compared to other countries. It can be concluded that research and publications related to this topic have made relatively little progress in the last five years. Model project based learning-STEAM terhadap kemampuan berpikir kritis dan literasi ilmiah siswa: Kajian bibliometrikPenelitian ini menganalisis penerapan model pembelajaran Project-Based Learning-STEAM (PjBL-STEAM) untuk meningkatkan kemampuan berpikir kritis dan literasi sains siswa khususnya di Indonesia, sehingga dapat diperoleh tren dan peluang penelitian terbaru tentang topik tersebut. Penelitian ini menggunakan pendekatan bibliometrik kuantitatif. Jumlah publikasi yang dianalisis adalah 142 dokumen publikasi tahun 2015-2020, metadata yang diperoleh dari database Scopus dan dianalisis menggunakan software VOSviewer. Hasil ekstraksi metadata menunjukkan terdapat 5 cluster dengan kata kunci yang paling banyak muncul adalah mahasiswa, pendidikan teknik, dan pendidikan STEM. Selain itu, hanya 0,5% penulis yang memiliki lebih dari dua publikasi, sehingga penelitian lanjutan dari publikasi sebelumnya tentang topik ini masih minim. Berdasarkan hasil pemeringkatan, Amerika Serikat menempati peringkat 1, Indonesia peringkat 2, dan Australia peringkat ketiga. Jika dibandingkan dengan negara lain, Indonesia unggul dalam pengembangan penelitian dan kolaborasi dalam topik ini. Dapat disimpulkan bahwa penelitian dan publikasi yang terkait dengan topik ini relatif sedikit mengalami kemajuan dalam lima tahun terakhir.